Expression of Mucin 2 Glycoproteins Forming the Mucosal Barrier of the Gut in Indonesian Indigenous Naked Neck Chickens and Normal Feathered Chickens - Ariyadi , B.; Sidadolog, J.H.P.; Harimurti, S.; Sudaryati, S.; Wihandoyo; Sasongko, H. (International Journal of Poultry Science, 2016)
Background: The cecum of the chicken gut may be susceptible to pathogens because it is readily colonized by microbes. The lower segment of the gut is also the primary tissue that permits the invasion of microorganisms from the external environment and the cloaca. Mucins, which are composed of glycoproteins, play significant roles in forming the barrier against infection on the mucosal surface. Objective: The aim of this study was to determine the differences in the mucosal barrier of the lower segment of the gut between Indonesian naked neck chickens and normal feathered chickens. Methodology: The lower segments of the gut (rectum, colon and cecal tonsil) of Indonesian indigenous naked neck chickens and normal chickens were collected. The expression of the mucin 2 gene in the gut mucosa was analyzed by reverse-transcription-polymerase chain reaction (RT-PCR). The localization and molecular sizes of the mucosal glycoproteins were analyzed by Western blot. Wheat Germ Agglutinin (WGA) and jacalin lectins were used for Western blot analysis. Results: The mucin 2 gene was expressed in the mucosal gut of the rectum, colon and cecal tonsil in both naked neck chickens and normal chickens. Western blot analysis showed a single band for both WGA and jacalin from the mucosal gut of the rectum, colon and cecal tonsil in both naked neck chickens and normal chickens. Conclusion: These results suggest that the mucin 2 gene and glycoproteins containing WGA and jacalin positive sugars cover the surface of mucosal gut in both naked neck chickens and normal chickens, most likely to form a mucosa barrier.